Signposts: New Directions in Southern Legal History - SALLY E. HADDEN, PATRICIA HAGLER MINTER (University of Georgia Press, 2013)
Nearly thirty years ago, James W. Ely Jr. and David Bodenhamer hosted a conference at the University of Southern Mississippi on southern legal history that invigorated a promising yet relatively unexplored subject. Prior to their conference, southern legal history was less visible as a fi eld, appearing only sporadically in history journals. Scholars working in the fi eld were few, and the â€œvastness of the research which remain[ed] to be doneâ€ was daunting. Ely and Bodenhamerâ€™s great shared complaint was the lack of legal history studies outside New England, which meant that â€œa body of literature from other regions still does not exist.â€ Such a critical omission made it â€œdiffi cult for historians to judge the appropriateness of current interpretations for diff erent sections of the country.â€ï›œ Their conference resulted in a 1984 book, Ambivalent Legacy. To this day, it remains the only broad work to collect research by southern legal historians working on an array of topics beyond race and slavery, for their volume also examined law and the regional economy as well as the southern bench and bar. Following that conference, scholars moved outward, investigating subjects ranging widely across the Southâ€™s legal history, and their work attracted new interest in the fi eld, which has grown steadily ever since. As part of the generation of legal historians inspired by this pioneering work, we believe that it is time to bring forward a collection of the newest research in southern law and history that demonstrates its dynamism and diversity. Signposts: New Directions in Southern Legal History is intended as a long- delayed successor to Ambivalent Legacy that hopes to inspire a new generation of scholarship in the fi eld while highlighting the exceptional work scholars are currently doing all over the South.